2001
DOI: 10.1210/mend.15.2.0595
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Nuclear Receptor-Interaction Domains and CREB-Binding Protein-Dependent Transactivation Function of Activating Signal Cointegrator-2

Abstract: ASC-2 is a recently isolated transcriptional cointegrator molecule, which is amplified in human cancers and stimulates transactivation by nuclear receptors, AP-1, nuclear factor kappaB (NFkappaB), serum response factor (SRF), and numerous other transcription factors. ASC-2 contained two nuclear receptor-interaction domains, both of which are dependent on the integrity of their core LXXLL sequences. Surprisingly, the C-terminal LXXLL motif specifically interacted with oxysterol receptor LXRss, whereas the N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
(123 reference statements)
2
25
0
Order By: Relevance
“…In addition, H3 and H4 acetylation were concomitantly induced (Fig. 4B and data not shown), as expected from the reported cross-talk between these 2 modifications (32,33) and between ASCOM and histone acetyltransferases CBP and p300 (34)(35)(36).…”
Section: Redundant Functions For Ascom-mll3 and Ascom-mll4 In H3ksupporting
confidence: 83%
“…In addition, H3 and H4 acetylation were concomitantly induced (Fig. 4B and data not shown), as expected from the reported cross-talk between these 2 modifications (32,33) and between ASCOM and histone acetyltransferases CBP and p300 (34)(35)(36).…”
Section: Redundant Functions For Ascom-mll3 and Ascom-mll4 In H3ksupporting
confidence: 83%
“…PKCa modulates LXRa transactivation reporter genes (Rochette-Egly 2003). Indeed, co-activators specifically modulating the function of LXR have been identified such as activating signal cointegrator-2 (Lee et al 2001). More recent findings have demonstrated that glucose signaling alters the sub-cellular distribution of LXR, although there is no evidence that this is phosphorylation dependent (Helleboid-Chapman et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that SREBP-1 facilitates the recruitment of coactivators to T0-901317-bound LXR&RXR complexes. LXRa, LXRb, and SREBP-1 interact with several coactivator proteins, including CREB binding protein (CBP) and the TRAP/ARC/DRIP complex (42)(43)(44)(45)(46)(47). We postulate that the presence of SREBP-1 on ACCa promoter 2 provides additional coactivator interaction sites that stabilize the binding of CBP, TRAP/ ARC/DRIP, and other coactivators to T0-901317-bound LXR&RXR.…”
Section: Discussionmentioning
confidence: 99%